2006
DOI: 10.1520/jai100408
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Release Characteristics of Alpine Ski Equipment

Abstract: Releasable bindings were developed to reduce the risk of lower leg injuries. However, the relationship between the incidence of specific alpine injury groups and the function and calibration of the release system has not been well understood. Over the 32 years between December 1972 and April 2004, the authors conducted a case control study at a northern Vermont ski area involving 17 967 injuries and 3617 uninjured controls. During that time, approximately 6.4 million skier visits were recorded at the area. Inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…No increase in injuries from inadvertent binding release through reduced binding settings has been found [21]. However, these findings mean an association, and not definitely "cause and effect" relationship, because another study at the same time showed a decrease in ACL injury risk without reducing binding settings [22] which might be due to the introduction of the short and shaped carving skis at this time [11]. Interestingly, the ISO 11088 standard accepts a deviation of 15% between the measured release moment ("reference moment") determined according to the setting tables in ISO 8061 and ski binding settings may also be lowered by the same magnitude upon request of the skier [23].…”
Section: Discussionmentioning
confidence: 92%
“…No increase in injuries from inadvertent binding release through reduced binding settings has been found [21]. However, these findings mean an association, and not definitely "cause and effect" relationship, because another study at the same time showed a decrease in ACL injury risk without reducing binding settings [22] which might be due to the introduction of the short and shaped carving skis at this time [11]. Interestingly, the ISO 11088 standard accepts a deviation of 15% between the measured release moment ("reference moment") determined according to the setting tables in ISO 8061 and ski binding settings may also be lowered by the same magnitude upon request of the skier [23].…”
Section: Discussionmentioning
confidence: 92%
“…However, Burtscher et al [2] showed that the gender specifi c knee injury rate remained constant with the introduction of carving skis while the overall injury rate has decreased by 9 % . In addition, Ettlinger et al [7] reported a signifi cant decrease in the risk of sustaining an ACL injury in recent years as carving skis became more popular. While ACL injury mechanisms on traditional skis are In recreational alpine skiing, ACL injury risk is 3 times greater in females.…”
Section: Introduction ▼mentioning
confidence: 99%
“…There are some indications that the incidence of ACL injuries in alpine skiing is aff ected by the introduction of the short and shaped carving skis. First of all, Ettlinger et al [7] reported a signifi cant decrease in the risk of sustaining an ACL injury in previous years when carving skis became more popular. In addition, other studies revealed even a lower risk for sustaining an ACL injury when skiing with carving skis compared to traditional skis [20,23] .…”
mentioning
confidence: 99%
“…In a case-control study, they found that lower binding release values in female skiers set 15 % lower than those recommended by the ISO 11088 standard would clearly reduce knee injuries in these persons (LaPorte et al, 2008). However, these findings mean an association, and not definitely a "cause and effect" relationship, because another study at the same time showed a decrease in ACL injury risk without reducing binding settings (Ettlinger, Johnson & Shealy, 2006) which might be partly due to the introduction of the short and shaped carving skis (Ruedl et al, 2011). Summing up, actual binding settings according to the ISO 11088 standard do not include a sex-related factor although females are skiing at lower mean speeds (Brunner et al, 2015;Shealy et al, 2005), showing an on average lower proportion of risk taking behaviour and having less muscle strength than males.…”
Section: Discussionmentioning
confidence: 96%